Respuesta :

Answer:

y=\left(\frac{1}{9}\right)x^2+\left(\frac{4}{3}\right)x+3

or

y=(1/9)x^2+(4/3)x+3

Step-by-step explanation:

let equation be:

ax^2+bx+c=y

(-9) as root:

81a-9b+c=0    -(1)

(-3) as root:

9a-3b+c=0     - (2)

Pass (-6,-1):

36a-6b+c=-1   - (3)

(2)+(3)

45a-9b+2c=-1    - (4)

(1)-(4)

36a-c=1

c=36a-1   -(5)

from (3)  

c=-1+6b-36a   -(6)

from (5) & (6)

36a-1=-36a+6b-1

72a=6b

12a=b     -(7)

(5) & (7) into (2)

9a-3(12a)+36a-1=0

9a=1

a=1/9     -(8)

from (7)  & (8)

b=4/3

from (5)  & (8)

c=3

answer:

y=(1/9)x^2+(4/3)x+3